Cardiomyopathy-Related Mutations in Cardiac Troponin C, L29Q and G159D, Have Divergent Effects on Rat Cardiac Myofiber Contractile Dynamics - Sampath K. Gollapudi; Murali Chandra (Biochemistry Research International)
Previous studies of cardiomyopathy-related mutations in cardiac troponin C (cTnC)—L29Q and G159D—have shown diverse findings. The link between such mutant effects and their divergent impact on cardiac phenotypes has remained elusive due to lack of studies on contractile dynamics. We hypothesized that a cTnC mutant-induced change in the thin filament will affect global myofilament mechanodynamics because of the interactions of thin filament kinetics with both Ca2+ binding and crossbridge (XB) cycling kinetics. We measured pCa-tension relationship and contractile dynamics in detergent-skinned rat cardiac papillary muscle fibers reconstituted with the recombinant wild-type rat cTnC (cTnCWT), cTnCL29Q, and cTnCG159D mutants. cTnCL29Q fibers demonstrated a significant decrease in Ca2+ sensitivity, but cTnCG159D fibers did not. Both mutants had no effect on Ca2+-activated maximal tension. The rate of XB recruitment dynamics increased in cTnCL29Q (26%) and cTnCG159D (25%) fibers. The rate of XB distortion dynamics increased in cTnCG159D fibers (15%). Thus, the cTnCL29Q mutant modulates the equilibrium between the non-cycling and cycling pool of XB by affecting the on/off kinetics of the regulatory units (Tropomyosin-Troponin); whereas, the cTnCG159D mutant increases XB cycling rate. Different effects on contractile dynamics may offer clue regarding how cTnCL29Q and cTnCG159D cause divergent effects on cardiac phenotypes.